Quantitation of ribavirin in human plasma and red blood cells using LC–MS/MS. Issue 5 (29th January 2014) - Ferreirós, N.; Labocha, S.; El‐Duweik, J.; Schlecker, C.; Lötsch, J.; Geisslinger, G.
<x xml:space="preserve">Abstract</x> LC–MS/MS has been applied for the rapid determination of the nucleoside analogue ribavirin in human plasma and red blood cells. The incorporation of ribavirin to the erythrocytes has been assayed after in vitro incubation of the cells at different concentrations of the antiviral drug. After protein precipitation, samples were injected into a C8 column, achieving a complete separation of ribavirin from the endogenous isobaric compound uridine. Calibration ranges varied from 10 to 10 000 ng/mL in plasma and from 0.2 to 200 ng/cell pellet in red blood cells. Precision and accuracy values were always below 10 and 13%, respectively, in all assayed matrices. Ribavirin was demonstrated to remain unchanged after short and long time storage. No matrix effects could be assessed for the analyzed matrices. The developed method has been fully validated. Monitoring of ribavirin concentration in red blood cells in addition to the classic plasma monitoring of the drug could help to explain its efficacy and safety profiles in patients.